1998
DOI: 10.1017/s0963548398003678
|View full text |Cite
|
Sign up to set email alerts
|

Uniquely Colourable Graphs and the Hardness of Colouring Graphs of Large Girth

Abstract: For any integer k, we prove the existence of a uniquely k-colourable graph of girth at least g on at most k12(g+1) vertices whose maximal degree is at most 5k13. From this we deduce that, unless NP=RP, no polynomial time algorithm for k-Colourability on graphs G of girth g(G)[ges ]log[mid ]G[mid ]/13logk and maximum degree Δ(G)[les ]6k13 can exist. We also study several related problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 16 publications
1
71
0
Order By: Relevance
“…But the results of the past few paragraphs suggest that for large enough ∆, perhaps it is true whenever χ(G) is sufficiently close to its upper bound of ∆(G) + 1. A construction from Embden-Weinert et al [11] shows that it is not true for some graphs with χ(G) = ∆ − ⌈ √ ∆⌉:…”
Section: The Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…But the results of the past few paragraphs suggest that for large enough ∆, perhaps it is true whenever χ(G) is sufficiently close to its upper bound of ∆(G) + 1. A construction from Embden-Weinert et al [11] shows that it is not true for some graphs with χ(G) = ∆ − ⌈ √ ∆⌉:…”
Section: The Resultsmentioning
confidence: 99%
“…This is well-known to be trivial for c ≤ 2. Embden-Weinert et al [11] used their construction (see Section 1.2) to prove that for 3 ≤ c ≤ ∆−k ∆ −1, we cannot test for c-colourability of graphs with maximum degree ∆ in polytime unless P = NP . On the other hand, Theorem 5 easily implies that for every constant ∆ ≥ ∆ 0 and every c ≥ ∆ − k ∆ , there is a linear time deterministic algorithm to test whether graphs of maximum degree ∆ are c-colourable.…”
Section: Algorithmic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no dichotomy is known for k-Coloring restricted to graphs of maximum degree at most d, but some partial results have been obtained. Molloy and Reed [60] classified the complexity for all pairs (k, d) for sufficiently large d, whereas Emden-Weinert et al [19] showed that k-Coloring is NP-complete for graphs of maximum degree at most k + √ k − 1. By combining the latter result with Brooks' Theorem [8], we find that the smallest open case is the following problem.…”
Section: Open Problem 4 Determine the Complexity Of Precoloring Extenmentioning
confidence: 99%
“…The question was refined in [86] to lattices and this paper also contains a polynomial algorithm (using Ramanujan graphs) which constructs for given k and l a graph G k,l with girth(G k,l ) = l and χ(G k,l ) = k (see also [22]). …”
Section: Proof Of Theorem 3 ([72])mentioning
confidence: 99%